Teacher spatial skills are linked to differences in geometry instruction. (31st August 2017) - Otumfuor, Beryl Ann; Carr, Martha
Abstract : Background: Spatial skills have been linked to better performance in mathematics. Aim: The purpose of this study was to examine the relationship between teacher spatial skills and their instruction, including teacher content and pedagogical knowledge, use of pictorial representations, and use of gestures during geometry instruction. Sample: Fifty‐six middle school teachers participated in the study. Methods: The teachers were administered spatial measures of mental rotations and spatial visualization. Next, a single geometry class was videotaped. Result: Correlational analyses revealed that spatial skills significantly correlate with teacher's use of representational gestures and content and pedagogical knowledge during instruction of geometry. Spatial skills did not independently correlate with the use of pointing gestures or the use of pictorial representations. However, an interaction term between spatial skills and content and pedagogical knowledge did correlate significantly with the use of pictorial representations. Teacher experience as measured by the number of years of teaching and highest degree did not appear to affect the relationships among the variables with the exception of the relationship between spatial skills and teacher content and pedagogical knowledge. Conclusion: Teachers with better spatial skills are also likely to use representational gestures and to show better content and pedagogical knowledge during instruction. Spatial skills predict pictorial representation use only as a function of content and pedagogical knowledge.